Pengetahuan Ibu dan Dukungan Suami berhubungan dengan Pemakaian Metode Kontrasepsi Jangka Panjang (MKJP) - Safitri Safitri (Jurnal Akademika Baiturrahim Jambi, 2021)
The public health center Pakuan Baru Jambi cityis the public health center with the lowerst uses a method of long-term contraception.The low use of long-term contraceptive methods can be caused by ignorance about the advantages of the MKJP and the obstacle of supporthusband in using the method. This study is a quantitative study, with a cross sectional design that aims todeterminethe relationship between mother’sknowledge and supporthusband to the use of MKJPin the public health center Pakuan Baru, Jambi city. Data collection on mother’sknowledge and supporthusband using a questionnaire.As many as 42study subjects were selected by simple random sampling. This study was analyzed using the chi square statistical test.The results of the study there is a relationship between mother’sknowledge and support husband to the use of MKJP, with mother’sknowledge p value = 0.036 and support husband p value = 0,000. The results of this study can be used as a rationale for policymaking in order to increase the number of long-term family planning acceptors